KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI KEGIATAN EKSTRAKURIKULER - Tri Hartono; Reni Untarti (Jurnal Math-UMB.EDU, 2020)
Each person has a different mathematical communication ability. Mathematical communication ability is a person's ability to convey information about mathematical concepts and ideas both in spoken and written form. This study aimed to describe the mathematical communication skills of students of Grade VIII of SMP Negeri 2 Purwokerto based on extracurricular activities. The type of this research was descriptive qualitative. The subjects used in this study were students of Grade VIII B SMP N 2 Purwokerto in the 2019/2020 academic year. Data were collected using the form of tests, interviews, and documentation. The test used in this study was a written mathematical communication skill test. The research subjects consisted of 2 students with academic extracurricular activities, 2 students with non-academic extracurricular activities, and 2 students with both academic and non-academic extracurricular activities. The results of this study indicated that: 1) students who only took academic extracurricular activities and students who took both academic and non-academic extracurriculars were able to present mathematical ideas in the form of images, mathematical symbols, and provide arguments for problems that were presented appropriately, and 2) students who only joined non-academic extracurricular activities, in general, had not provided arguments for a problem that was presented properly, but they were able to present mathematical ideas into the form of images and mathematical symbolsÂ appropriately.Keywords: Mathematical communication skills, extracurricular activities.